Revitalisasi Merit system dalam Pengangkatan Jabatan Fungsional di Badan Kepegawaian Daerah Jawa Tengah - Ahmad Faiz; Endang Larasati; Teuku Afrizal (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Changes in the management of human resources of the State Civil Apparatus (ASN) demand a policy based on the Merit system, namely the selection of the quality of the State Civil Apparatus (ASN) who has qualifications, competence and performance. This is particularly so in the appointment and filling of functional positions. However, in its implementation the merit system has not been implemented thoroughly due to employee competencies that are not in accordance with the requirements. Therefore, it is important to revitalize the merit system to rearrange employees according to their duties and functions, especially in functional positions. This research focuses on the revitalization of the Merit system in the appointment of functional positions to government employees. This study refers to Stahl's (1962) theory of merit systems by comparing qualifications, competencies and achievements that affect human resource selection. With a qualitative approach, this research was conducted in the Civil Service Agency of Central Java Province. Primary data collection is carried out through in-depth interviews and observation techniques, in addition to secondary data through archives and documentaries. The results showed that; (i) the process of filling and appointing Functional Positions is in accordance with the principles of the merit system, namely in accordance with the qualifications, competencies and formations required by the organization and the required job description assignments; . (ii) there is inpassing functional positions originating from administrative positions, especially those from executive positions and supervisory positions. This study concludes that the Merit Revitalization system in the Appointment and distribution of Functional Positions in the Central Java Regional Civil Service Agency has been implemented according to qualifications, competencies and formations. Research suggests (i) distribution of filling and appointment of functional positions to fill all areas or parts (ii) of tethering functional allowances for functional positions.